Class II antigen (HLA-DR) expression by intestinal epithelial cells in inflammatory diseases of colon. - McDonald, G; Jewell, D (1987)
Eighty four colonic biopsy specimens were obtained from patients with ulcerative colitis, Crohn's disease, radiation colitis, infectious colitis, and from normal controls. Paired specimens were examined by histological and immunohistochemical methods using monoclonal antibodies to the beta chain of HLA-DR antigen. The expression of HLA-DR antigen in mucosal epithelial cells was strongly related to whether the specimens were actively inflamed: epithelial cells from 34 of 37 inflamed specimens (nu three of 42 non-inflamed specimens) were HLA-DR positive (p less than 0.0001). Epithelial cells were uniformly HLA-DR negative in specimens from normal control patients despite the presence of HLA-DR positive lymphoid cells and macrophages in the lamina propria. Epithelial cells in specimens from patients with ulcerative colitis, Crohn's disease, and radiation colitis were HLA-DR positive in 30 of 33 inflamed biopsy specimens and in only three of 25 non-inflamed specimens (p less than 0.0001). Epithelial cells were HLA-DR positive in nine of 10 biopsy specimens from patients with acute infectious colitis (p less than 0.01).